Penanganan Crew Change di Kapal Mt Ocean Rih Pt. Pelayaran Semesta Sejahtera Lestari Belawan - Jeremy Yoshua Pratama Sinaga; Dafid Ginting (Journal of Management and Social Sciences, 2025)
Shipping agency services PT Pelayaran Semesta Sejahtera Lestari Belawan Medan is one of the shipping companies operating in the agency sector (Shipping Agency) in Indonesia. This company deals in quite a lot of ships, both Indonesian flag ships and foreign flag ships. Crew change is an important part of shipping operations that affects the safety, efficiency and performance of the ship. This research aims to analyze procedures and challenges in handling crew changes on ships, as well as identifying best practices to ensure crew changes run smoothly. The research methodology uses qualitative methods such as interviews with crew managers and analysis of crew change documentation data. The research results show that the main challenges in crew change include administrative obstacles, logistics and strict regulations. In addition, it was found that good implementation of Standard Operating Procedures (SOP), use of communication technology, and cross-departmental coordination are key factors for success in managing crew change. This research concludes the importance of collaboration between stakeholders, regulatory adjustments, and technological innovation to increase efficiency and safety in crew changes on ships.